Rifampicin-resistant Mycobacterium tuberculosis: susceptibility to isoniazid and other anti-tuberculosis drugs - Kurbatova, E V (2012)
Fil: Kurbatova, E V. Centers for Disease Control and Prevention, Atlanta, Georgia; Estados Unidos.